Relationship between learning ability and genotoxicity from organophosphate pesticide exposure among primary school children in Tanjung Karang, Selangor, Malaysia - Miswon, Nurul Husna (2016)
Introduction: Organophosphate pesticides (OPs) mainly malathion are used extensively in agriculture throughout the world and has been linked to neurodevelopmental deficit and genotoxic effect. The effects are particularly profound in children because at this phase they are active, their organ and systems especially their cognitive functions are developing. Depression of blood cholinesterase is used as a biomarker of the OPs toxicity. Objective: The aim of the study was to determine the relationship of organophosphate pesticides exposure with learning ability and genotoxicity. Methodology: A comparative cross-sectional study was conducted among 150 primary school children. They were selected as a study group as they went to school and lived near paddy field. Another 100 primary school children who were located further away from agriculture site served as the comparative group. The questionnaires were completed by their parents or caretakers. The children’s capillary blood was collected using finger prick. The blood cholinesterase levels were determined using cholinesterase test kit LOVIBOND 412870 AF287 and the McCarthy Scales of Children’s Abilities (MSCA) was used to determine the learning ability. Two assays were used to determine the chromosome breakage and DNA damage namely the micronuclei and comet assay. Buccal cells were collected from children for genotoxic effect. Result: There were significant differences (p<0.05) in blood cholinesterase, all scales in MSCA, micronuclei frequency and comet tail length between the study and the comparative group. There were significant relationships between blood cholinesterase and learning ability in all scales in MSCA (p<0.05). For genotoxicity assessment, only comet tail length showed significant relationship with blood cholinesterase (p<0.001). Other variable significantly influenced the blood cholinesterase and genotoxicity was distance from the house to paddy field (p<0.05). Blood cholinesterase was the most significant influencing factor on the all scales in the learning ability (p<0.05). Conclusion: Blood cholinesterase which indicates organophosphate pesticides exposure had significant relationship with the learning ability scales and genotoxicity in the study group.